Comparison of Triple-Tube Heat Exchanger and Spherical Ice Balls for Energy Storage Performance: A Numerical Study - Gülşah Karaca Dolgun (Energies)
Ice energy storage systems have gained significant attention as sustainable solutions for energy management, particularly in applications with fluctuating energy demands. This study aims to compare two different designs, a triple-tube heat exchanger (TTHE) and spherical ice balls, the latter being the most widely used traditional design in the industry. The TTHE design was first analyzed theoretically, then optimized using Computational Fluid Dynamics (CFD) simulations, and validated by the literature. Finally, it was compared with spherical ice balls under identical conditions. The analyses were conducted for an ice storage volume of 1000 kg, with the complete solidification process designed to occur within 8 h. The results indicate that the TTHE reduced solidification time by 25% while simultaneously increasing energy storage by 8%. This study contributes to the advancement of sustainable energy technologies by providing a comparative analysis of spherical ice balls and triple-tube heat exchangers for optimizing ice storage systems. The implementation of a TTHE for thermal storage can lower energy costs, mitigate peak demand, and address the intermittency challenges associated with renewable energy sources.